2020
DOI: 10.1055/s-0039-3402516
|View full text |Cite
|
Sign up to set email alerts
|

The Matrisome, Inflammation, and Liver Disease

Abstract: Chronic fatty liver disease is common worldwide. This disease is a spectrum of disease states, ranging from simple steatosis (fat accumulation) to inflammation, and eventually to fibrosis and cirrhosis if untreated. The fibrotic stage of chronic liver disease is primarily characterized by robust accumulation of extracellular matrix (ECM) proteins (collagens) that ultimately impairs the function of the organ. The role of the ECM in early stages of chronic liver disease is less well-understood, but recent resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 136 publications
0
21
0
Order By: Relevance
“…As mentioned, in some areas of research (e.g., subcutaneous wound healing), the global changes to the ECM in response to acute injury are well-understood. 16 In contrast, research on the hepatic ECM in the context of liver disease has been largely 'collagenocentric' and 'fibrosocentric,' or primarily focused on the role of the collagen ECM during fibrogenesis 65,66 (Fig. 1).…”
Section: Disruption Of the Architecture And Composition Of The Liver Ecm In Diseasesmentioning
confidence: 99%
“…As mentioned, in some areas of research (e.g., subcutaneous wound healing), the global changes to the ECM in response to acute injury are well-understood. 16 In contrast, research on the hepatic ECM in the context of liver disease has been largely 'collagenocentric' and 'fibrosocentric,' or primarily focused on the role of the collagen ECM during fibrogenesis 65,66 (Fig. 1).…”
Section: Disruption Of the Architecture And Composition Of The Liver Ecm In Diseasesmentioning
confidence: 99%
“…Even in cases where there is a net increase in ECM in liver (e. g. fibrosis), overall turnover is also increased [19]. Importantly, we and others have demonstrated that even acute alcohol-mediated experimental liver injury causes a robust change to the hepatic ECM [11,20].…”
Section: The Ecm Dynamic Remodeling and Disease Progressionmentioning
confidence: 49%
“…This definition has more recently been expanded to also include ECMaffiliated proteins (e. g., collagen-related proteins, transmembrane proteoglycans), ECM regulators and modifiers (e. g., lysyl oxidases, transglutaminases or matrix metalloproteinases) and secreted factors that bind to the ECM (e. g., Transforming growth factor β (TGFβ), and other cytokines) [8]; this expanded definition has been renamed the 'matrisome' [9]. The ECM not only provides structure and mechanical support for the cells in a tissue, but also acts as a reservoir for growth factors and cytokines and as a signaling hub through which cells can communicate with their environment and vice versa [7,10,11].…”
Section: The Ecm Dynamic Remodeling and Disease Progressionmentioning
confidence: 99%
“…Professor Gavin E. Arteel of the Department of Medicine and the Pittsburgh Liver Research Center at the University of Pittsburgh School of Medicine opened the first session by talking about the metabolism of the extracellular matrix in prefibrotic liver disease. His talk emphasized that there are many additional critical processes occurring in the extracellular matrix (ECM) of the liver during liver disease aside from collagen-and fibrin-dominated fibrosis 1) . He noted that the definition of "ECM" has recently expanded to include not only the fibrillar proteins themselves, but also many regulatory/ modifier proteins and secreted factors that reside in this matrix, which is designated as the "matrisome."…”
Section: St Sessionmentioning
confidence: 99%